2018
DOI: 10.1186/s12879-018-3395-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of herpes zoster and postherpetic neuralgia on the quality of life of Germans aged 50 or above

Abstract: BackgroundHerpes zoster (HZ) is a painful dermatomal rash caused by reactivation of latent varicella zoster virus surviving in the patient’s sensory ganglia after a previous episode of varicella. The incidence of HZ increases markedly with age as does the proportion of HZ patients who develop postherpetic neuralgia (PHN) with often severe and debilitating pain persisting for months and even years.This prospective study aimed to assess the impact of HZ and PHN on the quality of life (QoL) of individuals aged ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 44 publications
(50 reference statements)
1
37
0
1
Order By: Relevance
“…In our study, pain intensity had a both direct and indirect negative effect on QoL of patients with NeP, which meant with an increase in pain intensity, the QoL would decrease and this result was consistent with many previous studies (Cocchio et al, ; Curran et al, ; Melek et al, ). More importantly, our participants were composed of four kinds of disease‐causing NeP, which may exemplify pain more accurately than a specific disease‐causing NeP, a common trend in previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, pain intensity had a both direct and indirect negative effect on QoL of patients with NeP, which meant with an increase in pain intensity, the QoL would decrease and this result was consistent with many previous studies (Cocchio et al, ; Curran et al, ; Melek et al, ). More importantly, our participants were composed of four kinds of disease‐causing NeP, which may exemplify pain more accurately than a specific disease‐causing NeP, a common trend in previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Questionnaire compliance (in terms of response rates for completed questionnaires) in this study was lower than observed for other studies which used a similar approach to evaluating HZ impact on HRQL [25,26]. We had available ZBPI and EQ-5D scores for only around 50% of our cohort at initial assessment, and so our observations on pain and interference in ADLs and impact on HRQL may not be wholly representative of the overall study population.…”
Section: Discussionmentioning
confidence: 70%
“…Data on the severity of HZ pain and impact upon activities of daily living (ADL) and HRQL were collected through questionnaires as reported in similar previous studies in patients with HZ from international studies and in those conducted in Germany, Italy, and Japan [24][25][26][27] which used the validated Zoster Brief Pain Inventory (ZBPI) and the EuroQoL-5 Dimension (EQ-5D) questionnaires [4,7,28,29]. For assessment of subsequent pain, clinically relevant PHN was defined as the presence of HZassociated moderate or severe ''worst pain'' score C 3 on the ZBPI scale index persisting or appearing more than 90 days after onset of the rash [25][26][27]30].…”
Section: Data Collection and Patient Follow-upmentioning
confidence: 99%
“…PHN was defined as the presence of pain with NRS-11 ≥ 3 after 90 days of rash onset. A patient with pain intensity of NRS-11 < 3 or a patient whose treatment was terminated owing to pain disappearance was defined as non-PHN (19). Any complication that occurred within 3 months was recorded.…”
Section: Data Collection and Outcomesmentioning
confidence: 99%